A Quality Improvement Initiative to Improve Patient Safety Event Reporting by Residents. Issue 1 (21st January 2022) - Herchline, Daniel; Rojas, Christina; Shah, Amit A.; Fairchild, Victoria; Mehta, Sanjiv; Hart, Jessica
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Residents play a key role in patient care at academic medical centers and have unique insights into safety improvement opportunities. At our institution, <1% of safety events were reported by resident trainees. The primary objective of this quality improvement (QI) initiative was to increase the monthly incidence of event reporting by pediatric residents by 20% from baseline within 12 months. Methods: A QI team used the model for improvement to identify barriers to submitting safety event reports. The team used multiple intervention cycles to increase knowledge and promote engagement in event reporting. Interventions included educational tip sheets, a hospital-wide Morbidity and Mortality (M&M) conference, peer recognition and acknowledgment by senior leadership for report submission, and an interactive reporting activity. The outcome measure was monthly number of reports filed by residents. The process measure was the number of unique residents submitting a report each month. Time to complete a report was a balancing measure. Results: The number of reports placed by residents increased significantly, with a centerline shift from 15 to 29 reports per month (statistical process control chart—Fig. 3). The number of unique residents submitting reports increased from 10 to 22 per month. The time to complete a report was unchanged. Conclusions: Engaging residents in patient safety initiatives through education, experiential learning, and recognition can increase safety event reporting by residents. Future planned interventions include enhancing safety event reporting technology, developing patient safety faculty and resident champions, and increasing transparency regarding outcomes of safety event reports.